Intersecção de arte e design: a mediação pela artesania - Pantaleão, Lucas Farinelli; Pinheiro, Olimpio José [UNESP] (My University, 2010)
The language in the contemporaneous, for treating from essential factor to the communication and artistic expression, mainly starting from the intense expansion of the industrial techniques, it’s makes way for a considerable reflection: the stylistic relationship among the industrial object, the craft and the properly artistic work (DORFLES, 1988). The aesthetics, as inherent factor and mediator the all these subjects, is capable to establish similarities between the design concept and the contemporary art. Starting from this panorama an interpretative analysis is delineated on the function aesthetics/poetics (JAKOBSON, R. 1995; MUKAROVSKY, J. 1993) in the language of the design, under the optical of the contemporary thought in order to provide a contribution of updating of the present delimitation context between the art and the design in the extent of the aesthetics.

A linguagem na contemporaneidade, por se tratar de fator essencial à comunicação e expressão artística, principalmente a partir da intensa massificação das técnicas industriais, abre caminho para uma considerável reflexão: a relação estilística entre o objeto industrial, o artesanal e o propriamente artístico (DORFLES, 1988). A estética, como fator inerente e mediador a todos estes questionamentos, é capaz de estabelecer similitudes entre o conceito de design e a arte contemporânea. A partir deste panorama delineia-se uma análise interpretativa sobre a função estética/poética (JAKOBSON, R. 1995; MUKAROVSKY, J. 1993) na linguagem do design, sob a óptica do pensamento contemporâneo a fim de proporcionar uma contribuição de atualização do presente contexto de delimitação entre a arte e o design no âmbito da estética.
Keywords: Art; Design; Aesthetic function; Arte; Design; Função estética